Construction and practice of infection prevention and control system in large Fangcang shelter hospitals - ZHANG Yibo, WU Wenjuan, BI Yufang, JING Feng, GU Zhidong, YANG Zhitao, SHANG Hanbing, LIN Jingsheng, CHEN Erzhen (Zhenduanxue lilun yu shijian, 2022)
The management team from Ruijin Hospital had successively participated in the design, construction and operation of many Fangcang shelter hospitals. Combined with the large scale of the hospital, large amount of patients and medical wastes, high infection risk of staff, this paper summarizes the experience of our team in the prevention and control work from design of Fangcang shelter hospital, infection prevention and control system and operation process, staff training, health management, medical waste management, which may provide reference for the safe and stable operation of large shelter hospitals.